Good Public Governance as Intermediating of Confirmation Bias, Oversight, and Performance of Public Sector Financial Reporting (Architecture Image Studies, 2026)
The current research takes the mediating role of Good Public Governance (GPG) in the relationship between confirmation bias, oversight mechanisms and public sector financial reporting performance under forensic consideration. An explanatory quantitative study, where the primary data was obtained from 102 civil servants in charge of financial management and supervision working at the Muna regency government. Data were examined by SEM-PLS analysis. The results demonstrate that confirmation bias has a negative impact on good public governance, whereas internal control positively influences good public governance. On the other hand, there is no such effect for external monitoring. In addition, good public governance has significant positive effects on financial reporting performance and partially mediates confirmation bias, internal oversight (but not external oversight). Such results underline the significance of governance quality as an institutional channel that connects structural and behavioral factors with public sector performance, particularly in developing country local governments.